CHARACTERIZATION OF SALAK WEDI ACTIVATED CARBON STRUCTURE USING KOH AND ZnCl2 ACTIVATOR - Aprillia Dwi Ardianti; Rizka Nur Faila (ROTOR, 2023)
Activated carbon can be made from a variety of organic and inorganic raw materials. One of the organic materials with great potential in the manufacture of activated carbon is the bark of salak wedi(Salacca Zalacca). The purpose of this study was to determine the physical characteristics of the activated carbon of salak wedi peel which has been chemically activated using KOH and ZnCl2 with the process of being activated once using only KOH or ZnCl2 and multilevel activation using a combination of KOH and ZnCl2 to determine the number of pores in the sample and to determine the presence of a crystal structure in the sample. The research method includes sample making, single and multilevel activation processes, then SEM and XRD tests are carried out. The results of SEM with multilevel activation have more pores than the activated carbon sample of bark once. The SEM results obtained that the multilevel activation has a larger number of pores compared to the activation which is only carried out once, with the result that the largest pore volume with the stratified activator Carbon KOH + ZnCl2 (s) is 35,976,798,714 nm3. The XRD analysis indicated that activated carbon from the bark of salak wedi is a material with good conductivity properties because it has a relatively high crystalline structure, both on one-time activation and multilevel activation. Time using KOH activator obtained phase crystalline with the most significant percentage if compared with another activation.